Application of hydrogels in cancer immunotherapy: a bibliometric analysis - Liu, Xiang; Zhou, Qiang; Yang, Yue; Chen, Erhua (Frontiers in Immunology, 2024)
The field of cancer immunotherapy has significantly advanced in recent years, leading to an abundance of relevant studies globally. Cancer immunotherapy has made significant progress in recent years, with numerous studies worldwide. Utilizing immunotherapy for modulating the immune system has brought about a transformative impact on the fields of oncology and autoimmune diseases. Immunotherapy has had a transformative impact on oncology and autoimmune diseases. In the biomedical arena, hydrogels possessing favorable physicochemical characteristics are extensively employed in cancer immunotherapy hydrogels with good properties are widely used in cancer immunotherapy.Methods: From 2013 to 2023, a systematic search was conducted in the Web of Science Core Collection database to identify reviews and articles discussing the applications of hydrogels in cancer immunotherapy. The software CiteSpace was used to visually perform the bibliometric analysis in terms of research trends, countries, institutions, authors, journals, and keywords. Individual authors' productivity was assessed with the Lotka's law. The most relevant publication sources were identified by Bradford's law.Results: A total of English-language publications related to hydrogels in cancer immunotherapy were collected. The number of annual publications increased rapidly after 2021 and remained constant for the past two years. China published the most articles in this field. The institution with the maximum number of published articles was the Chinese Academy of Sciences in China. Chen. Q was the most prolific author, and Liu. Z was the second most published author. In terms of journal contributions, the journal "Biomaterials" had the highest number of publications (n = 30). Biomaterials, Advanced Functional Materials and Journal of Controlled Release were the most influential journals. Keyword analysis revealed that cancer immunotherapy, drug delivery, immunogenic cell death, tumor microenvironment, injectable hydrogels, and immune checkpoint blockade were the primary research hotspots. In recent 3 years, adoptive T-cell therapy, black phosphorus, cell capture, adaptive cell therapy, tumor microenvironment, photodynamic therapy, and sustained release were the research hotspots in this field. Our study summarizes the objective of hydrogels in cancer immunotherapy in recent years, providing a reference for potential researchers in related field.This bibliometric analysis shows the progress and trend of research on hydrogels in cancer immunotherapy.